2010
DOI: 10.1155/2010/402750
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Impact of Cyclosporin Reduction with MMF Treatment in Chronic Allograft Dysfunction: REFERENECE Study 3-Year Follow Up

Abstract: Calcineurin inhibitor (CNI) toxicity contributes to chronic allograft nephropathy (CAN). In the 2-year, randomized, study, we showed that 50% cyclosporin (CsA) reduction in combination with mycophenolate mofetil (MMF) treatment improves kidney function without increasing the risk for graft rejection/loss. To investigate the long-term effect of this regimen, we conducted a follow up study in 70 kidney transplant patients until 5 years after REFERENCE initiation. The improvement of kidney function was confirmed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 44 publications
1
6
0
Order By: Relevance
“…Patients with LAR had significantly inferior long‐term allograft survival. This observation echoed the findings in previous reports that LAR had a significantly negative impact on CAN and long‐term allograft outcomes . We were unable to demonstrate a significant difference in overall survival in patients with LAR.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Patients with LAR had significantly inferior long‐term allograft survival. This observation echoed the findings in previous reports that LAR had a significantly negative impact on CAN and long‐term allograft outcomes . We were unable to demonstrate a significant difference in overall survival in patients with LAR.…”
Section: Discussionsupporting
confidence: 82%
“…However, no long‐term outcomes were reported. Similar beneficial results with slowing of renal function deterioration without additional risk of acute rejections were also observed in patients with chronic allograft dysfunction with the use of high dose MMF(2 g daily), as in the Reference study and both high dose MMF(2 g daily) and Prednisolone (not less than 10 mg daily) in the Creeping Creatinine Study . Protocol biopsy has been suggested to help to select a low risk group which would benefit from CsA minimization without an increase in rejection .…”
Section: Discussionmentioning
confidence: 69%
“…No acute rejection episodes were observed, and only one patient in each group lost a graft. At 5 years, kidney function had improved in the MMF group, whereas it was impaired in the CsA group [16]. At 5 years, graft survival was 95.8% in the MMF group and 90.9% in the CsA group [16].…”
Section: Addition Of Mpa To Cnismentioning
confidence: 93%
“…A few studies have assessed the impact of reducing CNI dose on kidney function under the umbrella of introducing MPA . One of the largest studies conducted has been a French randomized prospective study that included 101 kidney transplant patients who had been recipients of a graft for at least 1 year and had presented with a negative slope of 1/serum creatinine .…”
Section: Cni‐sparing Protocols In Maintenance Kidney Transplant Patientsmentioning
confidence: 99%
“…22 In another approach, the cyclosporine dose was halved after the addition of MMF, which also resulted in stabilization of the renal function in the group with the reduced cyclosporine dose, whereas those on the full dose experienced progressive worsening. 23 Strategies with mTOR inhibitors have been published. 13,[24][25][26] To date, the most robust study demonstrated that patients with glomerular filtration rates (GFR) > 40 mL/min had improvement of renal function and lower rate of neoplastic diseases 24 months after conversion to sirolimus, compared with controls.…”
Section: Management Of Chronic Renal Allograft Disease (Crad)mentioning
confidence: 99%